2021
DOI: 10.5812/numonthly.117820
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Risk Factors of Hemodialysis Catheter Infection in Dialysis Patients: A Prospective Study

Abstract: Objectives: Infectious central venous catheter (CVC) complications, including mortality and care and hospitalization costs, are still a major clinical concern. This study aimed to determine the prevalence of hemodialysis catheter infection and its risk factors among hemodialysis patients. Methods: The present research was a descriptive, prospective cross-sectional study on hemodialysis patients in Babol hospitals during 2020 - 21. The participants' demographic information and some relevant data on clinical var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…(18,22,24) Despite the high rates of hypertension in patients with CRBSI, several studies reported there was no statistically significant effect of hypertension in CRBSI. (16,20) Comorbid hypertension was reported in two patients of this case series, and DM was reported in one patient.…”
Section: Discussion Smentioning
confidence: 59%
See 2 more Smart Citations
“…(18,22,24) Despite the high rates of hypertension in patients with CRBSI, several studies reported there was no statistically significant effect of hypertension in CRBSI. (16,20) Comorbid hypertension was reported in two patients of this case series, and DM was reported in one patient.…”
Section: Discussion Smentioning
confidence: 59%
“…Several studies reported more prevalent CRBSI in men than women. A study by Shoaib et al, reported 65.56% male subjects (14) , Yang et al, reported 62.07% male subjects (15) , and Nasiri et al, reported 68.18% male subjects (16) , but these differences were not statistically significant between infected and non-infected DL patients. The age of reported CRBSI also varied.…”
Section: Discussion Smentioning
confidence: 94%
See 1 more Smart Citation
“…Due to a high volume of cases and a dearth of surgical theatres, there are significant delays in the creation of AVFs. Studies indicate that the majority of patients begin dialysis treatment with temporary vascular catheters, which is regarded as a suboptimal method due to the associated inconvenience and the substantial risk of central-line-associated bloodstream infections [10,11].…”
Section: Lack Of Resources and Workforcementioning
confidence: 99%